Chinese traditional village residents' behavioural intention to support tourism: an extended model of the theory of planned behaviour. Issue 2 (13th July 2020) - Shen, Ke; Shen, Huawen
Abstract : Purpose: Based on the theory of planned behaviour (TPB), this paper aims to investigate the effects of residents' place attachment (PA), subjective norms (SNs) and perceived behavioural control (PBC) on their attitudes towards behaviour (AB) and behavioural intention to support tourism (BI). This paper aims to examine whether residents' AB mediate the relationships between BI and PA, SNs and PBC. Design/methodology/approach: The results are obtained using a quantitative method based on data gathered from self-administered questionnaires completed by 406 residents of Hongcun, a Chinese traditional village. Findings: The TPB is successfully used to explain Chinese traditional village residents BI. The findings extend the extant research and render the TPB more widely applicable. This study confirms that the inclusion of PA within the framework of the TPB is valid and satisfactory, demonstrating continued support for the coupling of complementary theories to explain tourism development from a resident perspective. Finally, this study extends the literature on residents' PA and demonstrates its impact on their attitudes and consequent reactions, thus supplementing the limited evidence on PA as a direct predictor of residents' BI. Specifically, SNs are the critical factor affecting residents' AB and their BI. Residents' AB only mediate the relationship between SNs and their BI. Research limitations/implications: This paper only includes PA within the framework of the TPB. More constructs should be incorporated to deepen the understanding of residents' BI. In addition, the data were only collected in a traditional village. Originality/value: This paper is one of the first studies to combine PA with the TPB in research on residents' BI in a developing country – in this instance, China. Abstract : 中国传统村落居民支持旅游行为意向: 基于拓展的计划行为理论: 摘要 研究目的: 基于计划行为理论, 本研究探索了传统村落居民之地方依恋、主观规范和感知行为控制对于其行为态度和支持旅游行为意向的影响作用; 同时本研究亦探究了居民之行为态度在地方依恋、主观规范和感知行为控制与其支持旅游行为意向之间的中介作用。 研究方法: 本研究采用定量的研究方法, 对从中国传统村落——宏村所收集到的406份有效问卷进行统计分析, 形成结论。 研究发现: 本研究发现计划行为理论能够成功解释中国传统村落居民支持旅游行为意向, 进一步拓展了该理论的运用范围。首先, 本研究将地方依恋纳入计划行为理论, 构筑两者之间的理论联系, 打通了原本相互之间独立的两个理论之间的理论逻辑关联, 为后续的相关领域的研究提供了更加扎实的理论依据; 其次, 本研究也进一步拓展已有关于居民地方依恋的研究, 也进一步验证了其对于居民行为态度和支持旅游行为意向的影响作用; 最后, 主观规范在对于居民的行为态度和支持旅游行为意向施最为重要的一个影响因素, 同时主观规范还可以通过行为态度间接影响支持旅游行为意向。 研究局限: 本研究仅仅将地方依恋纳入计划行为理论, 应当考虑将更多的影响因素纳入研究范畴, 同时, 本研究的样本仅仅在宏村一地收集, 后续研究应该扩大案例地的范围进行样本的收集。 原创性: 本研究是为数不多的将地方依恋纳入计划行为理论研究框架, 来探索发展中国家居民支持旅游行为意向的研究之一。 Abstract : Intención de comportamiento de los residentes tradicionales chinos de los residentes de las aldeas de apoyar el turismo: un modelo extendido de la teoría de la conducta planificadaPropósito: Basando en la teoría de la conducta planificada, este texto investiga los efectos de apego a un lugar, normas subjetivas y control conductual percibido de los residentes sobre sus actitudes hacia la conducta y hacia la intención conductual para apoyar el turismo. Este texto también examina si las actitudes de residentes hacia la conducta intervienen las relaciones entre la intención conductual para apoyar el turismo y apego a un lugar, normas subjetivas y control conductual percibido. Diseño/metodología/manera: Los resultados se obtienen usando un método cuantitativo basado en los datos recopilados de los cuestionarios autoadministrados completados por 406 residentes de Hongcun, un pueblo tradicional de china. Resultados: La teoría de la conducta planificada está utilizada exitosamente para explicar la intención conductual de los residentes de pueblo tradicional de China hacia el apoyo al turismo. Estas conclusiones extienden la investigación existente y deje que la conducta planificada sea aplicada más ampliamente. Este estudio confirma que la inclusión del apego al lugar dentro del marco de la teoría de la conducta planificada es válida y satisfactoria, demostrando el apoyo continuo para el acoplamiento de las teorías complementarias para explicar el desarrollo del turismo a partir de una perspectiva de residente. Finalmente, esta investigación extiende la literatura en el apego al lugar de los residentes y demuestra su impacto en sus actitudes y reacciones consecuentes, complementando así la evidencia limitada en el apego al lugar como un índice de previsión directo de la intención conductual sobre el apoyo al turismo. Especialmente, las normas subjetivas son factores clave que afectan las actitudes de los residentes hacia la conducta y su intención conductual sobre el apoyo al turismo. Las actitudes de los residentes hacia la conducta sólo intervienen la relación entre las normas subjetivas y su intención conductual sobre el apoyo al turismo. Implicaciones sociales: Este texto sólo incluye el apego al lugar dentro del marco de la teoría de la conducta planificada. Se debería incorporar más constructos para profundizar la comprensión sobre la intención conductual de los residentes sobre el apoyo al turismo. Además, los datos sólo fueron recopilados en un pueblo tradicional. Originalidad/valor: Este texto es uno de los estudios líderes que combina el apego al lugar con la teoría de la conducta planificada para investigar la intención conductual de los residentes sobre el apoyo al turismo en un país en desarrollo - en esta instancia, China.